Health literacy level among elderly and chronic disease self-management - Mirczak, Anna (Journal of Education, Health and Sport, 2017)
Introduction. Creating heatlh literacy is a new concept in the field of health promotion, which implies that a person will be managed to control own health. Health literacy is the degree to which individuals have the capacity to obtain, process and understand health information and services to make appropriate health decisions. There are three levels of health literacy: functional (basic), interactive and critical, which determine the health of the individual. Low health literacy, which is of particular concern among older adults, is negatively associated with health behaviors and health outcomes. In addition inadequate health literacy has been shown to be associated with several adverse health outcomes, such as mortality, hospitalization, and emergency care visits. Objective. The aim of this paper was to show the relationship between the level of elderly health literacy and process of chronic diseases self-management. Description of the state of knowledge. The level of health literacy is particularly important among older people suffering from chronic diseases including hypertension, atherosclerosis or diabetes. Health literacy have an influence on self-management process which means recognition of symptoms, medical adherence, take action in emergency ad many other. Summing up. Knowledge of health literacy in chronic diseases helps recognition of patient limitation in the process of obtaining and understanding health information. It also helps to properly design a therapeutic education for the individual, including all barriers. The ability of chronic disease self-management must be treated as an integral part of the patient treatment.